1996
DOI: 10.1038/sc.1996.134
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound bone densitometry and dual energy X-ray absorptiometry in patients with spinal cord injury: a cross-sectional study

Abstract: Bone is lost following spinal cord injury (SCI) and in the long-term may become osteopenic and liable to fracture. Two non-invasive techniques, ultrasound bone densitometry (USBD) and dual energy X-ray absorptiometry (DXA), have been applied to monitor bone changes after spinal injury. 31 SCI patients were scanned using an ultrasound bone densitometer, to give measurements of speed of sound (SOS), broadband ultrasound attenuation (BUA) and 'stiffness'. The time since injury of these patients ranged between 5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 17 publications
1
34
0
2
Order By: Relevance
“…19,20 This technique has been used in assessment of SCI and appears to be tolerated well by this population. 1,2,21 DEXA provides a precise and accurate measure of body composition, and unlike chemical testing, hydrodensitometry or anthropometry, gives a regional distribution of bone, fat and lean tissue mass. 19,22 The present short study was undertaken to examine bone and soft tissue changes, using DEXA, in a small group of male paraplegics in comparison with age-and height-matched able-bodied controls.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 This technique has been used in assessment of SCI and appears to be tolerated well by this population. 1,2,21 DEXA provides a precise and accurate measure of body composition, and unlike chemical testing, hydrodensitometry or anthropometry, gives a regional distribution of bone, fat and lean tissue mass. 19,22 The present short study was undertaken to examine bone and soft tissue changes, using DEXA, in a small group of male paraplegics in comparison with age-and height-matched able-bodied controls.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Of note, the literature is replete with reports of cross-sectional studies that have found, contrary to the extremities and other bony structures, that the vertebral column does not seem to lose bone mass after paralysis but, rather, tends to gain bone mass with age and/or longer duration of injury. 1,[7][8][9][10][11] Various mechanisms have been proposed to explain why the vertebral spine does not lose bone mass, and these include continued application of gravity-related forces, the effects of prolonged seated posture and a different mechanical function of the spine than that of the limbs. Two reports have previously challenged the notion that the vertebral bodies are spared from bone loss after paralysis.…”
Section: Introductionmentioning
confidence: 99%
“…The factors that affect bone metabolism after fracture are the invasiveness of surgery, the period of bed rest, the degree of fracture, immobilization, and the process of fracture healing [7,12,17,26,31]. In our study groups, there were no differences in the period of bed rest and BMD of the femoral neck.…”
Section: Discussionmentioning
confidence: 56%